2016
DOI: 10.1080/1828051x.2016.1249421
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a medical plant mix and probiotic on performance and health status of suckling Holstein calves

Abstract: This study was carried out to evaluate the effects of a medical plant mixture and probiotic on performance, blood parameters, digestibility of some nutrients, and health status of suckling Holstein calves. Thirty newborn calves (1-10 days) with 42 ± 8 kg of average birth weight were used in a factorial arrangement (3 Â 2) with 6 treatments and 5 replicate. The treatments were: (1) control diet, (2) control diet þ2g probiotic per day, (3) control diet þ 1.5% medical plant, (4) control diet þ1.5% medical plant þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 34 publications
7
25
0
2
Order By: Relevance
“…At the pre-weaning stage, ADG and FE were not different among treatments. These results concur with other studies in which probiotics or EO were fed to calves before weaning [35]. The significant increase in ADG and FE after weaning of EO-fed calves shows that there was a positive residual effect of EO 15 days after stopping supplementation with that additive.…”
Section: Discussionsupporting
confidence: 91%
“…At the pre-weaning stage, ADG and FE were not different among treatments. These results concur with other studies in which probiotics or EO were fed to calves before weaning [35]. The significant increase in ADG and FE after weaning of EO-fed calves shows that there was a positive residual effect of EO 15 days after stopping supplementation with that additive.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that oregano oil group calves consumed more 3.3 kg milk replacer, 1.98 kg hay and 2.4 kg concentrate feed than the control group (Table 2). Similar results were reported by Morrison et al (2010), Ünlü andErkek, (2013), Özalpaydin, (2014), Silper et al (2014), andSeifzadeh et al (2017), while Santos et al (2015) stated that oregano oil decreased the amount of consumption of milk replacer. These differences can be thought to be caused by the fact that essential oils are given to animals in different doses.…”
Section: The Hay Concentrate Feed and Milk Replacer Consumption Amounts Of Calvessupporting
confidence: 84%
“…Los ensayos clínicos realizados en la década pasada, demostraron que el 45 % de probióticos comercializados, tienen nula eficiencia de las BAL en la prevención de diarreas en becerras, e incluso parece que estos en lugar de favorecer, incrementaron la incidencia y severidad de diarreas (4,5) , y no hay respuesta para mejorar la ganancia diaria de peso y la conversión alimenticia (6,7) . En la actualidad estos mismos parámetros son similares por los laboratorios que comercializan probióticos en las unidades de producción ganadera lechera.…”
unclassified